Analysis of Regional Financial Independence towards Economic Growth and Human Development Index (Case Study : SWP Gerbangkertasusila Plus) - Fildza Amalina Qisthina; Moh. Khusaini; Setyo Tri Wahyudi (Wacana Journal of Social and Humanity Studies, 2019)
This study examines how the relationship of economic growth (PE) and human development index (IPM) to regional financial independence. Some of the results of previous studies show differences in research findings. This research was conducted in 12 regencies and cities included in the SWP Gerbangkertasusila Plus durung periode 2012 to 2017. To conduct testing, researchers used panel data regression analysis using the help of Eviews 9 and testing hypotheses simultaneously with the F-test and partial with t-test. The results of this study indicate that simultaneously the PE and IPM variables have a positive and significant effect on regionan financial independence, while partially only a positive and significant effect on regional financial independence, and for PE has a positive and insignificant effect on financial independence area.